2017
DOI: 10.1186/s12916-017-0828-2
|View full text |Cite
|
Sign up to set email alerts
|

Can incontinence be cured? A systematic review of cure rates

Abstract: BackgroundIncontinence constitutes a major health problem affecting millions of people worldwide. The present study aims to assess cure rates from treating urinary (UI) or fecal incontinence (FI) and the number of people who may remain dependent on containment strategies.MethodsMedline, Embase, PsycINFO, Cochrane Central Register of Controlled Trials (CENTRAL), CINAHL, and PEDro were searched from January 2005 to June 2015. Supplementary searches included conference abstracts and trials registers (2013–2015). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
71
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 27 publications
(28 reference statements)
3
71
0
5
Order By: Relevance
“…Urgency urinary incontinence (UUI) is a common and troublesome problem. Despite decades of research its cause is not well understood and it remains difficult to treat . We have shown that neither ultrastructural nor urodynamic changes adequately explain the causal mechanism of UUI or its response to behavioral therapy.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Urgency urinary incontinence (UUI) is a common and troublesome problem. Despite decades of research its cause is not well understood and it remains difficult to treat . We have shown that neither ultrastructural nor urodynamic changes adequately explain the causal mechanism of UUI or its response to behavioral therapy.…”
Section: Introductionmentioning
confidence: 93%
“…We have shown that neither ultrastructural nor urodynamic changes adequately explain the causal mechanism of UUI or its response to behavioral therapy. Others have focused on peripheral abnormalities, but none of these approaches has identified a cause of UUI or greatly improved treatment …”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, median cure rate after medical interventions for SUI and urgency UI is 82.3% and 49% respectively. Therefore, many patients are not cured and rely on continence products …”
Section: Discussionmentioning
confidence: 99%
“…Although urinary incontinence (UI) is seen 1.5-2 times more in women up to 80 years and after that age it is observed in both sexes in similar rate 5 Urinary incontinence is an important problem that leads to hygiene loss, pressure sores, sleep disturbance, sexual dysfunction, depression, social isolation, increased risk of fracture, impaired quality of life, and increase in the risk of being placed in a nursing home. 6,7 Many patients limit their social activity and this causes them to go away from their environment.…”
Section: Introductionmentioning
confidence: 99%
“…These are transient causes reminiscent with the initials of Delirium, infection, atrophic vaginitis, pharmaceutical, psychological, excess fluids, restricted mobility, stool impaction initials. 5 If incontinence persists after these transient causes have been ruled out and conditions have been improved, permanent causes should come to mind. The types of incontinence caused by these persistent causes include functional continence, stress incontinence, urge incontinence, mixed and overflow incontinence.…”
mentioning
confidence: 99%